Planar broadband antenna for 2G/3G systems - Ashutosh Singh Chauhan; Priyansh Kasyap; Ankit Gupta; Debani Prasad Mishra; Surender Reddy Salkuti; Seong-Cheol Kim (Universitas Ahmad Dahlan, 2022)
A planar antenna with broadband gestalt is presented for mobile networks. The structure of the antenna is made up of a folded dipole pair with an L-figure microstrip coupling line. The microstrip coupling along with the dipoles are attached on a similar substrate. The radiation parts are plotted at 1.7 GHz, 2.2 GHz, and 2.7 GHz. A flexible coaxial cable made of perfect electric conductor (PEC) material is attached to the L-figure microstrip whereas the outside conductor made up of RO4350B material is attached to the coplanar strip of line. The gain of the antenna is almost 9 dBi. The benefit of the planar structure is that it offers a simple feeding structure and compact size that is necessary for second generation (2G)/third-generation (3G)/long-term evolution (LTE) systems. Finally, the antenna proposed is designed by using computer simulation technology (CST) microwave studio.